Cellular and molecular effects of fipronil in lipid metabolism of HepG2 and its possible connection to non-alcoholic fatty liver disease - Pansa, Camila C. [UNESP]; Molica, Letícia R. [UNESP]; de Oliveira Júnior, Fabiano C. [UNESP]; Santello, Lara C. [UNESP]; Moraes, Karen C. M. [UNESP] (Wiley, 2024)
Nonalcoholic fatty liver disease (NAFLD) is a global public health problem that affects more than a quarter of the population. The development of this disease is correlated with metabolic dysfunctions that lead to lipid accumulation in the liver. Pesticides are one of etiologies that support NAFLD establishment. Therefore, the effects of the insecticide fipronil on the lipid metabolism of the human hepatic cell line, HepG2, was investigated, considering its widespread use in field crops and even to control domestic pests. To address the goals of the study, biochemical, cellular, and molecular analyses of different concentrations of fipronil in cell cultures were investigated, after 24 h of incubation. Relevant metabolites such as triglycerides, glucose levels, β-oxidation processes, and gene expression of relevant elements correlated with lipid and metabolism of xenobiotics were investigated. The results suggested that at 20 μM, the pesticide increased the accumulation of triglycerides and neutral lipids by reducing fatty acid oxidation and increasing de novo lipogenesis. In addition, changes were observed in genes that control oxidative stress and the xenobiotic metabolism. Together, the results suggest that the metabolic changes caused by the insecticide fipronil may be deleterious if persistent, favoring the establishment of hepatic steatosis.
Keywords: cell culture; detoxification processes; lipid metabolism; NAFLD; pesticide